PERKEMBANGAN E-SPORT PADA PELAJAR REMAJA USIA 13-16 TAHUN PADA MASA PANDEMI COVID-19 - Ayub Tatya Admaja; Yulis Agung Saputro (Journal Physical Health Recreation (JPHR), 2021)
E-Sport is part of a sport that has grown rapidly in the last 5 years and is a sport that is supported by the government in developing rapidly. The dilemma that occurs is that a student's psychic and physical changes are due to reduced physical activity and social contact due to more work from home or study at home. Researchers try to explore the consequences of student activities that are required to study at home due to the corona virus. The positive and negative impacts or pros and cons in the COVID-19 pandemic can be a blessing or a disaster depending on the perspective of the mind. Researchers try to examine the development of e-sports which is now starting to become popular and even an addiction for all ages from children to adults, and is supported by many athletes who have achieved world-class achievements in FIFA or Pro Evolution Soccer, PUBG, and other online games. The problem from the research is the basis why researchers are interested in researching by using a survey method to the point of view of students and the point of view of parents and the point of view of teachers / lecturers about the development of e-sports which is very popular today. This research data is on a regional scale such as the province of Yogyakarta and if possible will be distributed via google form to all corners of the country so that the data obtained is more diverse according to the point of view of each region according to the culture and circumstances of each region. This research will be very interesting because the issue taken is a national issue in the world of sports today. From this study, it can be concluded that children aged 13-16 years like to play online games, because: 1) Repel boredom 50%, 2) Gathering with friends 30%, 3) Get 20% achievement. Judging from the data, it is clear that the goals of E-Sport have not been fully achieved in Indonesia. Because it should be clear with Esports to hone intelligence thinking quickly and precisely by playing some games.